THE ROLE OF CITY AUTHORITIES IN CONTRIBUTING TO THE DEVELOPMENT OF URBAN SLUMS IN GHANA - R.S King; O. Amponsah (Journal of Construction Project Management and Innovation)
Urban planning in Ghana in the last few decades has been constrained by the rapid pace of urbanisation. Despite the prospects of urbanisation in economic growth and socio-political advancement, it has the tendency to generate unprecedented cultural, political, social and environmental challenges which limit the effectiveness of urban planning. Evidence the world over reveals that though there is no rigid blue-print for urban planning, the traditional planning practices have been renounced to contain the current trends in urban spread and development. In Ghana however, the traditional planning practices are still in use manifesting in poor coordination among urban planners and the use of obsolete city bylaws, which results in creating further urban problems such as slums development. The purpose of this paper is to demonstrate that poor coordination among city authorities and inflexible city bylaws and regulations could lead to the formation of slums. Quantitative and qualitative data on access to basic infrastructure and utilities were gathered from households, enterprise owners and community leaders at Old Fadama in Accra, Amui Dzor in Ashaiman and Akwatia Line in Kumasi, using semi-structured questionnaires and interview guides, respectively. Key informant interviews were also held with utility providers to understand how they work together as a team. The findings show that traditional bureaucratic cultures contributed to the development of informal settlements in Ghana. Electricity Company of Ghana, the Ghana Water Company Limited and the Town and Country Planning Department has not been working closely with slum dwellers that also form part of the urban milieu. Thus, access to basic life-sustaining utilities is limited and unplanned resulting in losses to the utility companies due to illegal tapping of such services. The paper concludes that where coordination among the city authorities is weak and regulations are inflexible, the development of slums is very fast and at an unprecedented rate, as is observed in the three informal settlements studied.